'Second chance learners': An exploratory study of the choices, constraints, values and aspirations of some adult women learners on courses in the Further Education sector - Suart, Rebecca (2015)
The Further Education (FE) sector provides adult learners with an opportunity to retrain or give a ‘second chance’ to acquire the skills that they missed out on at school leaving age. Recent government statistics suggest that the majority of enrolments in FE colleges are by adult learners, particularly women. Despite this, government funded research focuses narrowly on issues of employment, employability and the returns to investment of training adults. There is little empirical research detailing the broader benefits for women who participate in FE or represents their voice and experiences. This study takes an interpretative feminist approach to gain the perspectives of adult women learners about their educational values, career aspirations and the barriers they face to participating in education. Three FE colleges were visited for this study where nine learners were interviewed and this dissertation presents four of these as case studies. Access to women learners’ ‘voice’ was facilitated using feminist style in-depth life history interviews and life grids enabling them to tell their story as they saw it. Drawing on the Human Capabilities approach, feminist theories and learning identities. This study extends our understanding of the multiple benefits women gain in FE. Women reflect on how education has helped them to overcome adversity, resist oppression, regain confidence and improve well-being. The learners who are also mothers are committed to being a good role model to their children and providing economic stability. This study provides a new dimension of women learners presenting their capacity for agency, empowerment and transformation as a result of educational opportunity. The doctoral theses plans to extend this study by conducting interviews at two census points, alongside more detailed analysis of the structural constraints that impact on the learners’ ability to utilise their capabilities.